Muscling selection in swine and its effect on carcass traits - Wheat, J.D.; Kropf, Donald H.; Chang, C.H.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs farrowed in May, 1972, were the first born in the select and control lines. Performances of animals in the two lines were essentially the same. However, ham firmness and color differed significantly (P<0.0l) between lines, with those in the select line firmer and darker than those from the control line.
Swine Industry Day 1973 is known as Swine Day, 1973
Keywords: Swine; Muscling; Carcass traits; Performance; Ham firmness; Ham color